OSELTAMIVIR APPLICATION AMONG HIV-INFECTED CHILDREN, SUFFERING FROM THE FLU - Yu.A. Fomin; E.E. Voronin; M.Yu. Fomina; Yu.M. Subkhankulova; T.G. Surnina ("Paediatrician" Publishers LLC, 2007)
The article provides the Oseltamivir application experience in flu treatment among HIV-infected children. The researchers showed that Oseltamivir is an effective medication for the given category of patients, reducing duration of the catarrhal syndrome and intoxication signs. The undesirable phenomena related to the medication intake proved to be transient and called for no cancellation of its use. Key words: children, hiv infection, flu, Oseltamivir.